Body pigmentation of shrimp Cryphiops caementarius (Palaemonidae) with diets supplemented with marigold (Calendula officinalis) - Fuentes Muñoz, Adelhi (2021)
The aim of this study was to evaluate the body pigmentation of Cryphiops caementarius with diets supplemented with marigold (Calendula officinalis). Male shrimp were collected from the Pativilca river (Lima, Peru) and cultured in the laboratory in individual containers installed inside eight glass aquariums (55 L). One shrimp was stocked in each individual container and there were six culture containers in each aquarium. The experimental treatments were diets supplemented with 0, 100, 200 and 300 mg/kg of marigold flower flour. Each diet had two repetitions. The pigmentation of epidermal chromatophores and the carotenoids of the shrimp body were determined at 15 and 30 days. The total concentration of carotenoids in shrimp from the natural environment was 9.47 mg/kg. A higher pigmentation of the shrimp body was obtained with diets supplemented with marigold. The highest concentration (14.83 mg/kg) and accumulation (5.44 mg/kg) of carotenoids was achieved after 15 days of feeding with 300 mg/kg of marigold in the diet (p<0.05), compared to diets with 200 and 100 mg/kg of marigold (13.82 and 12.22 mg/kg concentration and 4.60 and 2.60 mg/kg accumulation, respectively). No shrimp increased the number of chromatophores, nor was there dispersion of epidermal chromatophores, but the colour of the chromatophores was yellowish brown with increasing marigold concentration in the diets. The reddish body of the shrimp after cooking was obtained with the highest supplementation of marigold in the diet, so it is possible to give added value to the shrimp before harvesting, which will have commercial and culinary importance.